The isolation, characterization endophytic bacteria from roots of local rice plant Kamba in, Central Sulawesi, Indonesia - Sri Sudewi; AMBO ALA; BAHARUDDIN; MUH. FARID (Society for Indonesian Biodiversity, 2020)
Abstract. Sudewi S, Ala A, Baharuddin, Farid M. 2020. The isolation, characterization endophytic bacteria on from roots of local rice plant Kamba in Central Sulawesi, Indonesia. Biodiversitas 21: 1614-1624. The local Kamba rice plants are cultivated by the Bada Valley people for generations by obtaining seeds from previous crops. This rice plant is able to survive even though it is cultivated with traditional cultivation techniques. The ability to survive is suspected because this local rice plant is associated with endophytic bacteria through a variety of mechanisms including being able to produce the IAA hormone and its ability to dissolve phosphate. This study aims to find endophytic bacteria that have the potential to produce IAA and phosphate solvents through morphological and physiological characterization (Gram reaction test with 3% KOH, catalase test, hypersensitivity reaction and hemolysis activity), screening of IAA-producing bacteria qualitative and quantitative, phosphate dissolution activity on Pikovskaya medium, and quantitative using a spectrophotometer. Endophytic bacteria isolates from Gintu give the highest yields in IAA production and phosphate solubility activity, namely RKGU11 and RKGU6, respectively at 4,905 mg L-1 and 10.984 mg L-1 so that it has the potential to be used as a candidate for biofertilizer agents in developing effective sustainable agriculture, respectively, efficient and environmentally friendly.